Cp violation analysis of $$D^0→ M^0 K → M^0(π ^± \ell ^\mp ν )$$ D 0 → M 0 K → M 0 ( π ± ℓ ∓ ν ) - Wen-Jie Song; Shi-Qi Wang; Qin Qin; Ya Li (European Physical Journal C: Particles and Fields)
Abstract CP violation in the charm sector is highly sensitive to new physics due to its small predicted value within the standard model. By this work, we investigated the CP violation in the cascade decay process $$D^0(t_1) → π ^0 K(t_2) → π ^0(π ^± \ell ^\mp ν )$$ D 0 ( t 1 ) → π 0 K ( t 2 ) → π 0 ( π ± ℓ ∓ ν ) . Our results indicate that the CP violation induced by the interference of unmixed D-meson decay amplitudes dominates, with a peak value reaching $$5 × 10^{-3}$$ 5 × 10 - 3 . This is one order of magnitude larger than the sub-leading contribution, namely the double-mixing CP violation. Furthermore, the CP violation in the decay channel with the semileptonic final state $$π ^- \ell ^+ ν _\ell $$ π - ℓ + ν ℓ is one to two orders of magnitude larger than that in the channel with $$ π ^+ \ell ^- \bar{ν }_\ell $$ π + ℓ - ν ¯ ℓ . We propose that the CP asymmetry of the combined two decay channels can be measured experimentally. The resulting value is approximately half of the CP violation observed in the $$π ^- \ell ^+ ν _\ell $$ π - ℓ + ν ℓ channel, with the dominant contribution still reaching the order of $$10^{-3}$$ 10 - 3 . This approach offers the advantage of eliminating the need for flavor tagging of the initial D meson, thereby avoiding associated efficiency losses.